Strategi Bertahan Hidup Rumah Tangga Nelayan di Desa Bontolebang Kecamatan Galesong Utara Kabupaten Takalar - Hasriyanti; Maisarah Munirah Latief; Ernawati S. Kaseng (JURNAL ENGGANO, 2026)
This study aims to find out what opportunities exist in fishing villages to diversify jobs as a strategy to maintain survival in Bontolebang Village, Galesong District, Takalar Regency, how are the efforts made by fishing families to diversify these jobs, and what kinds of jobs are fishermen's families and anyone (family members) involved in the work. Furthermore, interpretation is carried out by giving meaning, explaining patterns or categories and also looking for interrelationships between various concepts. The results of the study stated that the strategy carried out was to adapt, diversify jobs, empower fisherwomen and female heads of household (WKRT) fishermen as much as possible, both related to fishing activities and outside. The possibility to diversify occupations depends on the available resources in the fishing villages. Each fishing village has different characteristics of the natural environment.